Pengaruh risiko litigasi, ketidakpercayaan investor, dan financial leverage terhadap kualitas pelaporan keuangan dengan komite audit berkeahlian hukum sebagai pemoderasi - Handayani, Windi Antika; Wahyudi, Ickhsanto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of litigation risk, investor distust proxied by institutional commissions and financial leverage as proxied by Debt to Equity Ratio (DER) on the quality of financial reporting proxied by accrual earnings managemeny by measuring the Stubben (2010) model through an approach to discretionary review and audit committee of legal experts as moderating variables. This research uses quantitative causality method. The sample consists of 28 manufacturing companies from the consumer goods industry on the Indonesia Stock Exchange in 2019-2020. Samples were taken using a purposive sampling technique, and data analysis using the SmartPLS 3.0 application. The results of the study prove that there is a significant influence on litigation risk with the quality of financial reporting. In addition, the results of the study do not prove that there is an effect on investor distrust and financial leverage with the quality of financial reporting. Then this study shows the results that the audit committee of legal experts cannot moderate the effect of litigation risk, investor distrust and financial leverage on the quality of financial reporting in consumer goods companies on the Indonesia Stock Exchange in 2019-2020.